The Impact of the Outward and Inward FDI on Global Value Chains - Su, Hang; Fu, Yao (International Journal of Economics and Financial Issues, 2021)
What kind of trade agreements should a country choose? Regional trade agreements, multilateral trade agreements, or both? What's the role of a country's outward foreign direct investment (OFDI) and foreign direct investment (FDI) in its participation and position in global value chains (GVCs)? Is a country's research and development spending conducive to breaking the "low-end locking" of FDI? Based on the World Input-Output Tables (WIOTs) released in 2016, this paper computes the indicators of GVC participation and position and identifies the feature of the production division, providing a reference for promoting regional and multilateral trade agreements. This paper uses feasible generalized least squares (FGLS) and system generalized method of moments (SYS-GMM) to examine the impact of a country's outward and inward FDI on its GVC participation and position. The empirical results imply that a country's OFDI promotes its GVC participation and fosters its upgrading within industries in GVCs, while FDI inhibits the upgrading of GVCs, though it promotes a country's GVC participation. In addition, a country's research and development spending can be conducive to breaking the "low-end locking" effect of FDI. Keywords: Outward Foreign Direct Investment, Inward Foreign Direct Investment, Global Value Chains, World Input-Output Tables, Feasible Generalized Least Squares JEL Classifications: C33, F21 DOI: https://doi.org/10.32479/ijefi.11950